2019
DOI: 10.1016/j.appet.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Duration of breastfeeding is associated with emotional eating through its effect on alexithymia in boys, but not girls

Abstract: A B S T R A C TEmotional eating (EE), or eating in response to negative emotions, was earlier shown to be associated with difficulty in identifying emotions (alexithymia). To improve our understanding of possible causes of alexithymia and EE, we assessed possible associations with duration of breastfeeding in infancy. The aim of the present study was to examine in a prospective, longitudinal study whether duration of breastfeeding is associated with EE in adolescence, through its effect on alexithymia difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…For instance, Goldschmidt and colleagues explored the relationships between emotional regulation, dietary restraint, and unhealthy eating in children, demonstrating a significant connection [40]. Similarly, a longitudinal study by Van Strien and colleagues [41] found that emotional eating in children increased over time in response to stress. These studies have predominantly centered on the role of negative emotions, with less emphasis on the influence of positive emotions [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Goldschmidt and colleagues explored the relationships between emotional regulation, dietary restraint, and unhealthy eating in children, demonstrating a significant connection [40]. Similarly, a longitudinal study by Van Strien and colleagues [41] found that emotional eating in children increased over time in response to stress. These studies have predominantly centered on the role of negative emotions, with less emphasis on the influence of positive emotions [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%